Silent Coup: How Corporations Overthrew Democracy - Provost, Claire; Kennard, Matt (London Bloomsbury Academic, 2023)
"As European empires crumbled in the 20th century, the power structures that had dominated the world for centuries were up for renegotiation. Yet instead of a rebirth for democracy, what emerged was a silent coup - namely, the unstoppable rise of global corporate power. Exposing the origins of this epic power grab as well as its present-day consequences, Silent Coup is the result of two investigative journalist's reports from 30 countries around the world. It provides an explosive guide to the rise of a corporate empire that now dictates how resources are allocated, how territories are governed, and how justice is defined"--
Includes bibliographical references and index.
Keywords: Business and politics; Big Business; Democracy; Big business; International business enterprises; Democracy